Aggressive Odontogenic myxoma: a case report - Yanelis Suárez Conde; Jordanis Viamontes Beltrán; René David Morales Basulto; Alicia María Hernández Suárez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Introduction: the odontogenic myxoma belongs to the group of tumors of odontogenic origin; they can cause visible deformities in the facial area. Objective: to expose clinical aspects of a patient with odontogenic myxoma. Case presentation: a clinical case is reported from white male patient, 25 years old, with no apparent personal pathological history is reported. He went to the body of guard of the Manuel Ascunce Domenech Hospital with an inflammatory process of sudden appearance in the right facial region, to the interrogation he referred asymptomatic, with slight limitation to the oral opening, with difficulty for phonation and swallowing. A week after starting the medical treatment, the evolution was not favorable, so it was decided to perform computed tomography in which a large hypodense image was observed that involved the right mandibular branch. The histopathological study reported odontogenic myxoma. It was decided to perform tumor reduction and possible surgical treatment, however, this entity had an aggressive evolution and the patient dies less than two months after diagnosis. Conclusions: the peculiarity of this case was the aggressive and infiltrating behavior of this entity, therefore, it was evident the variability in the clinical behavior of the odontogenic myxoma that despite being described as a benign tumor, had a torpid and unfavorable evolution for the patient.